Wetting Agent Influence on Water Infiltration into Hydrophobic Sand: I. Rewettability. (1st September 2014) - Song, Enzhan; Schneider, Joseph G.; Anderson, Stephen H.; Goyne, Keith W.; Xiong, Xi
Abstract : Soil water repellency causes non‐uniform water infiltration at slow flow rates, which leads to localized dry spot (LDS) on golf course putting greens. Wetting agents are the primary tool used to reduce soil water repellency on golf courses. Field experiments evaluating the efficacy of wetting agents often result in inconsistent conclusions due to variable environmental conditions, management intensity, and level of hydrophobicity. This study used octadecylamine treated sand, which exhibits stable and consistent water repellency, to test the influence of six commercially available wetting agents on water infiltration and sand rewettability. Replicated and repeated experiments were conducted using an infiltration tube system with a 4.4‐cm ponding depth ( h o ). Results showed that Cascade Plus, Tournament‐Ready, and Hydro‐Wet solutions exhibited significantly faster infiltration with steady flow rates at 35 mm min −1 or more, followed by Revolution and LescoFlo Ultra with a 25 mm min −1 steady flow rate. All treatments enhanced infiltration, but rewettability varied among tested wetting agents following drying cycles at 55°C until treated sand columns reached a constant weight. After three dry–wet cycles, LescoFlo Ultra treated sand exhibited the best rewettability with a steady flow rate at 34 mm min −1 . In contrast, treatment with Surfside 37 resulted in limited rewettability; water did not infiltrate after the second dry–wet cycle. Results suggest that there are significant differences in infiltration and rewettability among the wetting agents tested in this study. It is advised that specific management needs deserve consideration before selecting the appropriate wetting agent.